Implementasi Media Komik Digital Dalam Pembelajaran Akidah Akhlak di Pondok Pesantren Darul Ulum - Sumiati S; Deswalantri D (Madani: Jurnal Ilmiah Multidisiplin, 2025)
niches will be interesting, digital novel tools are also equipped with concepts & diversity of note styles so that they provide more innovative & innovative views. This research is a descriptive study with a qualitative approach that means describing the results of the application of the use of digital novel tools in the teaching of Moral Beliefs at the Darul Ulum Islamic Boarding School. The results of the study prove that the Teaching of Moral Beliefs at the Darul Ulum Islamic Boarding School with the help of digital novel tools is very helpful in the way of practicing & guiding. For teachers, digital novel tools are very efficient to use throughout the teaching of moral beliefs. Students also master each module that will be presented faster. Not only will the form be held in an interesting digital novel, it is also equipped with Islamic religious values for experts, so that it makes it easier for students & teachers to master the module. Therefore, the application of the use of digital novel tools in teaching Moral Beliefs at the Darul Ulum Islamic Boarding School provides important participation.